The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1103/physrevlett.99.126402
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Fluctuations in the Different Phases ofLaVO3andYVO3

Abstract: We investigate the importance of quantum orbital fluctuations in the orthorhombic and monoclinic phases of the Mott insulators LaVO3 and YVO3. First, we construct ab-initio material-specific t2g Hubbard models. Then, by using dynamical mean-field theory, we calculate the spectral matrix as a function of temperature. Our Hubbard bands and Mott gaps are in very good agreement with spectroscopy. We show that in orthorhombic LaVO3, quantum orbital fluctuations are strong and that they are suppressed only in the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
141
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(163 citation statements)
references
References 42 publications
21
141
1
Order By: Relevance
“…These are further split by the deviations from cubic symmetry. 21,27,[54][55][56] In cubic approximation, the lowest-lying two-electron state shows . 57 The cubic approximation is sufficient for the overall assignment of all RIXS peaks observed above 1 eV at the V L 3 edge.…”
Section: Crystal Structure Magnetic and Orbital Orders And Crymentioning
confidence: 99%
See 1 more Smart Citation
“…These are further split by the deviations from cubic symmetry. 21,27,[54][55][56] In cubic approximation, the lowest-lying two-electron state shows . 57 The cubic approximation is sufficient for the overall assignment of all RIXS peaks observed above 1 eV at the V L 3 edge.…”
Section: Crystal Structure Magnetic and Orbital Orders And Crymentioning
confidence: 99%
“…For RVO 3 with t 2 2g electron configuration, it has been suggested that orbital quantum fluctuations may be comparatively strong because superexchange interactions between t 2g electrons are frustrated on a cubic or nearly cubic lattice. 3,5,[27][28][29] From magnetic neutron scattering, indications for highly unusual orbital correlations were found and the existence of an orbital Peierls state in the intermediate phase of YVO 3 has been proposed. 3 However, a recent study of the optical excitations across the Mott-Hubbard gap rules out that orbital fluctuations are strong in RVO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Also, the Mott transition in LaVO 3 and YVO 3 occurs before orbital polarization is complete. 10 Moreover, in a hypothetical tetragonal structure of LaTiO 3 , relevant for heterostructures, the Mott phase is reached when n xz,yz approaches 1/4 and n xy vanishes. 11 Finally, the possibility of so-called orbital-selective Mott transitions in multiband systems has been discussed extensively in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the precise nature of correlated orbital states, being either of ordered or liquid type, and their existence in different materials is intensely debated, which to a large part is due to the fact that orbital correlations turn out to be very difficult to detect experimentally. In fact, such experimental access would be of great help in unraveling the puzzling properties of many systems with orbital degrees of freedom, for instance the above mentioned iron-pnictide materials, where the type of the orbital ordering or its lack is heavily debated [5][6][7] or titanium and vanadium oxides where different theoretical scenarios -a rather exotic orbital liquid phase [8,9], or a classical alternating orbital-ordered state [10,11] have been proposed.…”
mentioning
confidence: 99%